The French exception - Gouguet, J.-J.; Primault, D. (Journal of Sports Economics, 2006)
Currently, professional football in Europe is in a deep financial crisis. Amidst the five major European leagues (England, France, Germany, Italy, Spain), only France is not in a bad situation despite this country suffering from a low level of the demand from fans and a weakness in the urban system. The aim of this article is to show how the better regulation of the French organization explains this success. This organization is based upon three pillars: solidarity (revenue sharing), training (by all clubs), and financing control. Finally, the question is to know whether such a system should be extended throughout Europe.